Susiha a video documentary on the role of media ecology in the recognition of junior kilat in the National Media Industry - Goboy, Liz Stelle Gale T.
This study is a case study on how the presence of electronic age in media ecology helped in the national recognition of the Bisaya band, Junior Kilat. The researchers wanted to look at the characteristics and music of the band since they were the first Bisaya band to be nationally recognized in the new millennium. The study first determined the content and form of the band, followed by the discussion of the role of electronic age in the band?s national recognition and its implications on the relationship of media ecology and music. The study used the media ecology theory by Marshall McLuhan (1982). The proponents interviewed experts: 2 from the academe, 3 from the Bisaya music industry, 4 Bisaya music fans and enthusiasts, and all the current members of the Junior Kilat. The proponents also did online and library research. The study found out that it is the band?s unique concepts, lyrics, and genre that make them appeal to the audience. It was also found out that advancement of media technologies led to the easier propagation of the band?s music to a larger scope of audience. Furthermore, the study proved that music is an effective channel for communication. The video documentary discussed the characteristics of media ecology and its contribution to the national recognition of the Junior Kilat.